Expectations of Students to Improve their Academic Performance: Case Study - Paulina SPANU; Mihaela ULMEANU; Cristian DOICIN; Roxana MECHNO (Communications of International Proceedings, 2020)
Dropping out of school is a real problem, especially among first-year students, both at European and national level. In this context, the purpose of the research was to identify the main factors that determine Romanian students to drop out of college. Based on this results, it was identified solutions, means and tools useful in reducing the high dropout rate and increasing the academic performance of students. An online questionnaire was applied within the project ``E-tutoring: web tools and resources for study and career management`` in order to identify the main needs of students. The analysis of the data collected was performed using the Qualitative Content Analysis. The result of the analysis highlighted the fact that the main factors that contribute to school dropout are generated by financial problems, teaching methods, inappropriate choice of specialization and lack of support for counseling. The results demonstrate the need for an innovative system, based on peer learning and a lifelong career approach.
Keywords: career guidance; Cronbach's alpha; students` drop out